The Relationship between Intensity of Smartphone Use and Nomophobia Incidence - Aisyah, Bunaiya Siti (Jurnal Ilmu Kesehatan Abdurrab, 2024)
The use of smartphone has increased rapidly in recent years, which can cause problems. This study aims to determine the relationship between the intensity of smartphone use and the incidence of nomophobia. This study used descriptive correlation design and cross sectional approach. The sample of this study was 257 respondents who were taken based on inclusion criteria using proportionate stratified random sampling technique. The analysis used was bivariate analysis using the Spearman Rho test. The most results were 215 respondents had the intensity of smartphone use in the moderate category, as many as 8 respondents experienced mild nomophobia (3.7%), 140 respondents experienced moderate nomophobia (65.1%), and 67 respondents experienced severe nomophobia 31.2%). The results of the Spearman Rho test showed that there was a significant relationship between the intensity of smartphone use and the incidence of nomophobia, with a p value (0.000) < Î± (0.05), with a correlation coefficient of r = 0.377 (moderate relationship) with a positive direction, which means that the higher the intensity of smartphone use, the higher the level of nomophobia. The intensity of smartphone use has a significant relationship with the incidence of nomophobia.